Pengaruh Kompetensi dan Independensi Aparat Pengawas Interns Pemerintah (APIP) Terhadap Efektivitas Audit Internal pada Inspektorat Daerah Kabupaten Sukabumi - Cliff Natanael; Vicky Dzaky C. Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of good governance principles in local government administration requires an effective, professional, and independent internal control system. Government Internal Supervisory Apparatus (Aparat Pengawasan Intern Pemerintah – APIP) plays a strategic role in ensuring accountability and transparency in regional financial management. However, the effectiveness of internal auditing still faces various challenges, particularly related to auditor competence and independence. This study aims to analyze the effect of APIP competence and independence on internal audit effectiveness at the Regional Inspectorate of Sukabumi Regency. This research employs a quantitative approach using primary data collected through questionnaires distributed to APIP personnel. Data analysis was conducted using multiple linear regression analysis. The results indicate that APIP competence has a positive and significant effect on internal audit effectiveness. Furthermore, APIP independence also has a positive and significant effect on internal audit effectiveness. Simultaneously, competence and independence significantly influence internal audit effectiveness. These findings emphasize that internal audit effectiveness is strongly determined by the synergy between auditors’ professional competence and independence. Therefore, enhancing auditor competence through continuous training and strengthening auditor independence within the organizational structure are essential strategies to reinforce the internal audit function in local government.